Developing Standards for Language Teacher Education Programs in Indonesia: Professionalizing or Losing in Complexity? - Luciana, Luciana (TEFLIN Journal, 2004)
Setting standards for language teacher education programs, liletEI7al5, and evaluation sparks some hope n attempts to improve the quality of the programs. Yet, this very fact augmented by my eaaminaUOn of ten language teacher education programs in Java. Bali, and Lampung (FKIP and PGRI) triggers a critical look at the idea of standard development. In particular, I would like to explore whether it can lead to a better professionalism or we are just lost in the complexity of the standardization itself. This paper consists of four sections. De-parting from an overview of language teacher education programs in Indonesia and the theoretical foindatioils, some major problems in this area are identified. Following this, the discussion is focused on the idea of standard development for language teacher education pro-grams in Indonesia. Eventually, some suggestions are put forth to highlight the need for establishing coherent curriculum framework bridging the two realms of language teacher education and school ini-Iieu as well as providing learners with knowledge base that enables them to cope with complex demands of school settings and more essentially, to act as an agent in the social change process.